Surgical tactics in the treatment of gastrointestinal stromal tumors of the duodenum - A. Yu. Korolkov; T. O. Nikitina; D. N. Popov; A. O. Tantsev (Вестник хирургии имени И.И. Грекова)
We present the clinical case of the patient with gastrointestinal stromal tumor of the duodenum (dGIST).The 34-year-old women had complaints of intermittent dull pain located in the upper abdomen. Clinical examination of the abdomen revealed a duodenum tumor. Resection of the anterior wall of the descending part of the duodenum with a tumor was performed. Histopathology reported that the removed neoplasm was represented by GIST of the duodenum. Immunohistochemistry reported that the tumor cells had an expression of DOG 1, Vim, CD117, CD 34.